The world's fastest Indian [videorecording (DVD)] - Donaldson, Roger; Hopkins, Anthony, 1937-; Ladd, Diane; Lawford, Christopher Kennedy, 1955-2018 (Magnolia Pictures, 2005)
Burt Munro, a Kiwi from far south New Zealand has been building and rebuilding his motorcycle for the last 40 years, dreaming of the day when he and the bike can go to Utah's Bonneville Salt Flats and see what they can really do. When Burt's heart goes bad on him, his dreaming is threatened to come to an end. Luckily, Burt is not ready to stop dreaming. He decides to mortgage his house and bring his dream to life. He and the motorcycle head for American to participate in 'Speed Week'. His journey from Long Beach to Utah brings him through a cross section of American 'characters'. Each recognizes in Burt, that burning desire to achieve a dream and each helps him in the way that they can to make that dream happen. When Burt finally stands on Bonneville Salt Flats, by himself thinking of all the greatness that has transpired here and now he, Burt Munro, can at last test himself on this 'sacred ground'